If you could solve the equation in the title (and show me how) I'd be very greatful. Thanks.

Results 1 to 11 of 11

- Apr 3rd 2006, 01:29 PM #1

- Joined
- Mar 2006
- Posts
- 2

- Apr 3rd 2006, 02:05 PM #2

- Joined
- Nov 2005
- From
- New York City
- Posts
- 10,616
- Thanks
- 10

Originally Posted by**garybarlow**

$\displaystyle 4\sin z+\cos z=0$

Thus,

$\displaystyle 4\sin z=-\cos z$

Thus,

$\displaystyle 16\sin^2 z=\cos^2 z$

Thus,

$\displaystyle 16\sin^2 z=1-\sin^2 z$

Thus,

$\displaystyle 17\sin^2 z=1$

Thus,

$\displaystyle \sin^2 z=1/17$

Thus,

$\displaystyle \sin z=\pm \sqrt{1/17}$

Now cheack,

Notice that $\displaystyle \sin z=\sqrt{1/17}$ does not check with the first equation.

However, $\displaystyle \sin z=-\sqrt{1/17}$ does.

Thus, you need to solve,

$\displaystyle \sin z=-\sqrt{1/17}$ for all $\displaystyle z$

- Apr 5th 2006, 10:01 AM #3

- Joined
- Apr 2006
- Posts
- 6

- Apr 5th 2006, 01:08 PM #4

- Joined
- Nov 2005
- From
- New York City
- Posts
- 10,616
- Thanks
- 10

- Apr 6th 2006, 12:08 AM #5

- Joined
- Apr 2006
- Posts
- 6

- Apr 6th 2006, 02:00 AM #6
## a little trouble!

Well, actually when you are dealing with trigonometric complex functions, a standard trick is to substitute for exponentials. Remember

$\displaystyle

{\rm e}^{iz}-{\rm e}^{-iz}=2i{\rm sin}z, \ {\rm e}^{iz}+{\rm e}^{-iz}=2{\rm cos}z

$

and after substitution

$\displaystyle

(1-4i){\rm e}^{iz}+(1+4i){\rm e}^{-iz}=0

$ or $\displaystyle

{\rm e}^{2iz}=\frac{15-8i}{17}

$

(check this please! calculations are not my strong point )

so the solution is

$\displaystyle

2iz={\rm log}\left(\frac{15-8i}{17}\right)

$ or

$\displaystyle

z=-\frac{i}{2}{\rm log}\left(\frac{15-8i}{17}\right)$

so that

$\displaystyle z=

-\frac{i}{2}

\left({\rm log}\left|\frac{15-8i}{17}\right|+i{\rm Arg}\left(\frac{15-8i}{17}\right)+2k\pi i\right)$,

where the logarithm is the usual real one, $\displaystyle {\rm Arg}$ the principal argument and $\displaystyle k$ an integer.

- Apr 6th 2006, 02:47 AM #7

- Joined
- Apr 2006
- Posts
- 6

I've not learnt about the exponential stuff you can do with trigonometric equations like that yet.

I thought of another way to solve it

4 sin z + cos z = 0

let:

4 sin z + cos z = k cos(z - a)

4 sin z + cos z = k cos a cos z + k sin a sin z

k sin a = 4

k cos a = 1

=> tan a = 4

a = 1.33

4 sin z + cos z = k cos(z - 1.33)

k = sqrt(4^2 + 1^2)

k = sqrt(17)

4 sin z + cos z = sqrt(5) cos(z - 1.33)

so now you need to solve

sqrt(17) cos(z - 1.33) = 0

- Apr 6th 2006, 03:01 AM #8

- Apr 6th 2006, 03:10 AM #9

- Joined
- Apr 2006
- Posts
- 6

- Apr 6th 2006, 03:50 AM #10

- Apr 6th 2006, 05:59 AM #11

- Joined
- Nov 2005
- From
- New York City
- Posts
- 10,616
- Thanks
- 10